Philippine Literary Resources that Appeal to Gen Z Audiences’ Motivation to Read and Learn - Rolly G. Salvaleon; Maria Lady Sol A. Suazo; Abundio C. Miralles; Annie Y. Samarca; Jason V. Chavez; Liza D. Belandres; Sar-Ana M. Abdurasul; Rasmil T. Abdurasul (Environment and Social Psychology, 2025)
Reading motivation significantly shapes how individuals engage with texts, influencing academic achievement, language development, and critical thinking. This study examined how Philippine literary resources influence the reading and learning motivation of Generation Z (Gen Z) students, who are often more immersed in digital and global content than in local literature. Guided by Self-Determination Theory (SDT), the study explored how autonomy, competence, and relatedness are fostered through engagement with culturally grounded narratives. An exploratory qualitative design was used, with seventeen purposively selected Gen Z students participating in semi-structured interviews. Reflexive thematic analysis was employed to interpret their insights and lived experiences. Findings revealed that Philippine classical literature fosters emotional and psychological resonance through relatable characters, cultural values, and timeless themes. Students demonstrated growing autonomy in literary interpretation, competence in dealing with linguistic complexity, and relatedness through shared cultural meaning. They developed greater comprehension, critical awareness, and civic reflection as they connected literary experiences with personal and social realities. While limited by a small and homogenous sample, the study adopts a cautious interpretation of literature’s transformative potential and emphasizes the contextual factors that shape student motivation. Overall, the findings underscore the value of integrating culturally relevant texts and dialogic approaches in instruction to sustain intrinsic reading motivation and holistic learner development.